Changes in Smoking-Related Norms in Bars Resulting from California’s Smoke-Free Workplace Act - Satterlund, Travis D. (2012)
California’s Smoke-Free Workplace Act— CA Labor Code Sec. 6404.5(a)—was extended to bars in 1998. This paper analyzes changes in normative beliefs and behaviors related to bar smoking in the decade following the adoption of the Act. In a series of studies evaluating the smoke-free workplace law in bars, researchers conducted extensive observations and interviews with bar staff and patrons, health officials, and law enforcement personnel in three California counties. Smoking outside became a normal pause in the social environment and created a new type of bar socializing for outside smokers. Although some bar owners and staff reported initially resenting the responsibility to uphold the law, once norms regarding cigarettes and smoking began changing, bar workers experienced less conflict in upholding the law. Non-smoking behavior within bars also became the normative behavior for bar patrons. California’s Smoke-Free Workplace Act has both reflected and encouraged normative beliefs and behaviors related to smoking in bars. The findings indicate that such shifts are possible even in contexts where smoking behaviors and attitudes supporting smoking were deeply entrenched. Recommendations include attending to the synergistic effect of education and policy in effective tobacco control programs.